Basic building measurement - Marsden, Paul Kingsley, 1945- (New South Wales University Press, 1998)
An introductory text for tertiary students studying the measurement of building works. This new edition contains basic information, practical examples and exercises in building measurement. -- Provided by publisher.
Includes index.
Keywords: Building -- Australia -- Measurement.; Building -- Australia -- Measurement -- Problems, exercises, etc.; Buildings -- Specifications -- Australia.; Quantity surveying -- Australia.; elektronické knihy; electronic books